Legal Analysis from Postponement Debt Payment Obligations Vision Land Semarang Ltd.: Causal Factors and Resolution Steps - Prasasti Dyah Nugraheni (The Indonesian Journal of International Clinical Legal Education, 2025)
Vision Land Semarang Ltd. is a company in the textile industry export sector and is domiciled in Semarang Regency. Where in the year 2023, Vision Land Semarang Ltd. is experiencing a Postponement from Debt Payment Obligations (PDPO) filed by Konesia Prologix Line Ltd. domiciled in Central Jakarta through the Commercial Court in the Semarang District Court. This scientific article will discuss the causal factors and resolution steps taken by Vision Land Semarang Ltd. in resolving the problem from Postponement from Debt Payment Obligations (PDPO) experienced by that contained in the Commercial Court Decision Number: 5/Pdt.Sus-PKPU/2023/PN.Niaga.Smg. This scientific article uses a research method in the form from a normative juridical with laws and regulations as primary legal materials and scientific articles, books, a court decision, and online websites as secondary legal materials. The causal factors for the Postponement from Debt Payment Obligations (PDPO) experienced by Vision Land Semarang Ltd. consist from internal and external factors. Meanwhile, the settlement steps implemented by Vision Land Semarang Ltd. are to hold a meeting with Concurrent Creditors to discuss the Peace Proposal and Peace Plan which ends with the ratification from the Peace Agreement which is ratified (Homologated) by the Panel from Judges in the Commercial Court in the Semarang District Court.